Freudian mythologies Greek tragedy and modern identities - Bowlby, Rachel, 1957- (Oxford University Press, 2007)
Rachel Bowlby suggests that, with the multiplication of sexual roles, family forms, and reproductive technologies, Freud's 'Oedipus complex' may have lost its relevance. This book takes two Freudian routes to think about some of the entanglements of identity.